The abundance of prospective natural food for sea cucumber Holothuria atra at Karimunjawa Island waters, Jepara, Indonesia - RETNO HARTATI; WIDIANINGSIH WIDIANINGSIH; AGUS TRIANTO; MUHAMMAD ZAINURI; AMBARIYANTO AMBARIYANTO (Society for Indonesian Biodiversity, 2017)
Hartati R, Widianingsih, Trianto A, Zainuri M, Ambariyanto. 2017. The abundance of prospective natural food for sea cucumber Holothuria atra at Karimunjawa Island waters, Jepara, Indonesia. Biodiversitas 18: 947-953. Holothuria atra, as one of the most abundant and widely distributed sea cucumber species, is an omnivore, consuming detritus, uneaten food, and algae in the substrate. For sea ranching purpose, the objective of present works was aimed to determine potential food availability for H. atra in Karimunjawa Island of Jepara. Biotic environment factors in proposed location were assessed including seaweed and seagrass associated communities, epiphytes on the seagrass, phyto and zooplankton, benthic organism, microphytobenthic as chlorophyll-a, phaeophytin and chloropigmen as well as sediment characteristics. There were six species seagrasses and 10 species of seaweeds found in Karimunjawa waters, with Enhalus acoroides and Thalassia hemprichii provide shelter and food for H. atra. Algal epiphytes use seagrass leaves and rhizome as substrate and there were 28 genera of them belong to Chrysophyta, Chlorophyta, and Cyanophyta. The variety and abundance of phytoplankton, zooplankton the benthos enrich the location. The chlorophyll-a, phaeophytin and total chloropigment in the sediment of Karimunjawa waters could be representative of microphytobenthos. The substrate of Karimunjawa waters consisted of fine sandy-coarse sediment and the content of organic matter may be important for feeding activity of H. atra.